2005
DOI: 10.1002/chir.20198
|View full text |Cite
|
Sign up to set email alerts
|

Atropisomeric property of 1‐(2,6‐difluorobenzyl)‐3‐[(2R)‐amino‐2‐phenethyl]‐5‐(2‐fluoro‐3‐methoxyphenyl)‐6‐methyluracil

Abstract: 1-(2,6-Difluorobenzyl)-3-[(2R)-amino-2-phenethyl]-5-(2-fluoro-3-methoxyphenyl)-6-methyluracil (6), a potent and orally active antagonist of the human gonadotropin-releasing hormone receptor, exists as a pair of atropisomers in solution, which was detected by NMR spectroscopy, and separable by HPLC. In addition to a (R)-configured benzylamine, there is a second stereogenic element due to the presence of a chiral axis between the substituted 5-phenyl group and the uracil core. The rate constant of the interconve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…If the barrier to atropisomerization of a compound is low (class 2, Figure ), then one should consider developing the drug as a consistent and reproducible interconverting mixture . This is the case for Sch 40120 ( 11 ) (Scheme ), which is an inhibitor of 5-lipoxygenase.…”
Section: Atropisomeric Drugs: Medicinal Chemistry and Manufacturing P...mentioning
confidence: 99%
See 1 more Smart Citation
“…If the barrier to atropisomerization of a compound is low (class 2, Figure ), then one should consider developing the drug as a consistent and reproducible interconverting mixture . This is the case for Sch 40120 ( 11 ) (Scheme ), which is an inhibitor of 5-lipoxygenase.…”
Section: Atropisomeric Drugs: Medicinal Chemistry and Manufacturing P...mentioning
confidence: 99%
“…A further example of this strategy is provided in Scheme , where removal of the methyl from the central ring resulted in changing from a class 2 compound to class 1 compound . These uracil compounds are potent antagonists of the human gonadotropin-releasing hormone receptor.…”
Section: Atropisomeric Drugs: Medicinal Chemistry and Manufacturing P...mentioning
confidence: 99%
“…Further experiments using NMR and HPLC demonstrated that the interconversion between the two rotamers (aR-and aS-13) is fast, with a half-life estimated to be about 46 min at 37 °C in aqueous solution. 56 The X-ray crystal structure of 13 shows that the 2-fluoro-3-methoxyphenyl ring is nearly orthogonal to the uracil ring in the solid state (Figure 6), supporting the low-energy conformation and slow rotation of the biaryl bond. 55 An attempt to replace the 2-fluoro-3-methoxyphenyl group with various heteroaromatic groups to eliminate atropisomers while retaining potency resulted in some interesting compounds (Figure 7).…”
Section: Sar and Pharmacophore Of Uracil And Related Compoundsmentioning
confidence: 80%
“…In comparison, the des-fluoro analogue 14 ( K i = 2.3 nM) exhibits a single set of resonances under similar conditions. Further experiments using NMR and HPLC demonstrated that the interconversion between the two rotamers (a R - and a S - 13) is fast, with a half-life estimated to be about 46 min at 37 °C in aqueous solution . The X-ray crystal structure of 13 shows that the 2-fluoro-3-methoxyphenyl ring is nearly orthogonal to the uracil ring in the solid state (Figure ), supporting the low-energy conformation and slow rotation of the biaryl bond …”
Section: Sar and Pharmacophore Of Uracil And Related Compoundsmentioning
confidence: 86%
“…However, no further publication regarding this class of derivatives has been reported since. Secondly, the methyl group at 6-position was removed [ 48 ]. A table of potent uracil derivatives without 6-methyl group were then prepared (compounds 19 – 21 ).…”
Section: Small Molecule Gnrh Receptor Antagonistmentioning
confidence: 99%